Land Use and Social Economic Transformation in Colomadu Sub-District - Kusumaningrum, Ratna (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2015)
Urbanization turns out to be the most popular term use now to describe urban development and growth. In the process of urban development, sprawl is the stage when urban cannot provide the basic need of its inhabitant and then start to exploit the neighborhood area. The most obvious condition of urban sprawl is when the activities transforming from farm to non-farm activities (Zaninetti, 2006). Then turn the physical characteristic of the area and create a mixture of rural and urban land use characteristic. Area with this characteristic called as transitional area (Douglas, 2006 stated in Huang, Wang, Budd, 2009), peri-urban interface (Dutta, 2012) or desakota by Mcgee. As one of Solo City pery-urban area, Colomadu Sub district has been transforming both in land use and social economic characteristic. Colomadu is a unique area where administratively state as part of Karanganyar District but geographically located closer toward Solo City. So that, how is the land use and socio economic transformation there?.